2018
DOI: 10.1111/ijd.14138
|View full text |Cite
|
Sign up to set email alerts
|

Acne prevalence in 9 to 14‐year‐old old patients attending pediatric ambulatory clinics in Italy

Abstract: Acne is not a rare disease in pre-adolescent age. Adequate and prompt treatment is also needed in this class of patient to minimize disease burden and potential future disease worsening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
(43 reference statements)
1
12
1
1
Order By: Relevance
“…The evaluation of acne severity in our study showed that severe acne (GEA scale 4) was the most common form, found in 33% of cases. These results differ from those of Napolitano et al (2018) , who reported that 88.5% of examined children had mild or almost clear acne, suggesting that moderate-to-severe forms of the disease are very rare in the preadolescent age range. Our results are in accordance with a study that reported that experiencing a higher number of comedones or inflammatory lesions before puberty is associated with the subsequent development of severe acne ( Lucky et al, 1997 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The evaluation of acne severity in our study showed that severe acne (GEA scale 4) was the most common form, found in 33% of cases. These results differ from those of Napolitano et al (2018) , who reported that 88.5% of examined children had mild or almost clear acne, suggesting that moderate-to-severe forms of the disease are very rare in the preadolescent age range. Our results are in accordance with a study that reported that experiencing a higher number of comedones or inflammatory lesions before puberty is associated with the subsequent development of severe acne ( Lucky et al, 1997 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In the paper by Davis et al (2013) , 55 million pediatric acne visits took place over a 6-year period, and preadolescent acne accounted for 4.8% of acne cases. Another prospective observational study conducted in Italy showed that acne prevalence was lowest in 9-year-old children (6%; Napolitano et al, 2018 ). In our study, female patients were more affected (75%) than male patients (25%), as previously reported ( Napolitano et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiology of acne continues to evolve with changes in hormone levels that vary with age. An Italian study of pediatric outpatients aged 9-14 found that 34.3% patients had acne, with the lowest prevalence rate of 6% at age 9, and the incidence of acne increased to 36.3% after the age of 13 (24). From the prevalence of acne among Chinese adolescents, we found increased age was related to higher prevalence and severity of acne vulgaris: 15.6, 44.9, and 70.4% for 10, 13, and 16 years old (25).…”
Section: Agementioning
confidence: 99%
“…But it appears before the age of 12 in 32–40% of cases [ 13 ]. And acne is often associated with adolescence but can appear at any age, especially in the prepubertal period [ 14 ].…”
Section: Discussionmentioning
confidence: 99%